Architectural engineering design : mechanical systems - Butler, Robert Brown (New York : McGraw Hill Education, 2002)
Each title provides the architectural and design professional with a comprehensive reference of more than 1100 equations illustrated with both a large and small building example. Trademarked "no math menus" and shortcut 'recipes' allow any building element to be sized quickly and efficiently. Provide guidance on structural systems, materials, plumbing, electricity, illumination, and acoustics.
Chapter 1: Introduction -- Chapter 2: Climatic Forces -- Chapter 3: Climate Control -- Chapter 4: Plumbing -- Chapter 5: Electrical -- Chapter 6: Illumination -- Chapter 7: Acoustics.
Includes index.
Keywords: BUILDINGS ELECTRIC -- EQUIPMENT